Identification and characterization of profilin gene family in rice - Yanli Zhang (Elsevier, 2021)
Background: Profilin proteins (PRFs) are small (12–15 kD) actin-binding protein, which play a significant role in cytoskeleton dynamics and plant development via regulating actin polymerization. Profilins have been well documented in Arabidopsis, Zea mays L. as well as Phaseolus vulgaris, however no such fully characterization of rice (Oryza sativa L.) profilin gene family has been reported thus far. Result: In the present study, a comprehensive genome-wide analysis of rice PRF genes was completed and three members were identified. OsPRF1 and OsPRF2 shared 98.5% similarity (6 nucleotide divergence), but the deduced amino acid sequences of OsPRF1 and OsPRF2 are fully identical. In contrast, the OsPRF3 presents relatively lower similarity with OsPRF1 and OsPRF2. Phylogenetic analysis also support that OsPRF1 has a closer relationship with OsPRF2. Expression pattern analysis revealed the differential expression of OsPRFs in tissues of mature plant, which suggested the potential spatial functional specificity for rice profilin genes. Subcellular localization analysis revealed the OsPRFs were localized in cytoplasm and nucleus and all of them could bind actin monomers. Furthermore, abiotic stresses and hormones treatments assay indicated that the three OsPRF genes could be differentially regulated, suggesting that OsPRF genes might participate in different stress processes in rice. Conclusions: Taken together, our study provides a comprehensive analysis of the OsPRF gene family and will provide a basis for further studies on their roles in rice development and in response to abiotic stresses.How to cite: Zhang Y, Dong G, Wu L, et al. Identification and characterization of profilin gene family in rice. Electron J Biotechnol 2021;54. https://doi.org/10.1016/j.ejbt.2021.08.004.